Clinical value of 18F-fluoro-dexoxyglucose positron emission tomography/computed tomography in patients with adult-onset Still's disease: A seven-case series and review of the literature. Issue 4 (July 2014) - Yamashita, Hiroyuki; Kubota, Kazuo; Takahashi, Yuko; Minamimoto, Ryogo; Morooka, Miyako; Kaneko, Hiroshi; Kano, Toshikazu; Mimori, Akio
Abstract Objectives. While there are a few reports describing 18F-fluoro-dexoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) findings in patients with adult-onset Still's disease (AOSD), no summary report has yet been published. In this study, we evaluated the usefulness of FDG-PET/CT for diagnosis and activity evaluation in patients with AOSD by summarizing the findings of our patients and those reported in the literature. Methods. Seven consecutive AOSD patients who had undergone PET/CT at our department between 2007 and 2012 were included. We evaluated FDG uptake for characteristic findings in patients with AOSD. In addition, we reviewed the literature on seven previously reported AOSD patients who had undergone PET/CT. Results. FDG accumulation was positive mainly in the bone marrow (100%), spleen (90.9%), lymph nodes (80.0%) and joints (75.0%). In addition, FDG uptake was positive in the pericardium, pleura, salivary glands, eyelids, muscle and major blood vessels. Six patients underwent follow-up FDG PET/CT for evaluation of treatment efficacy. Follow-up PET/CT showed diminished FDG accumulation in the bone marrow, spleen and lymph nodes, with maximum standardized uptake value (SUVmax) being substantially reduced from 4.03 ± 0.95 to 2.20 ± 0.75 (p = 0.04), 4.04 ± 1.10 to 2.55 ± 1.13 (p = 0.04) and 5.63 ± 4.99 to 2.10 ± 1.91 (p = 0.11), respectively. No significant correlation was found between SUVmax in each lesion and the laboratory data, except for a significant correlation between lactate dehydrogenase (LDH) and spleen SUV. Conclusions. FDG-PET/CT is useful for long-term assessments of AOSD activity in individual patients. However, PET/CT findings alone are not sufficient to make a differential diagnosis of AOSD versus malignant lymphoma.